Hubungan Antara Presepsi Siswa Terkait Kompetensi Keperibadian Konselor dan Sikap Siswa Terkait Pelayanan BK - Maria Sensiliana Netu; Eem Munawaroh (Universitas Hamzanwadi, 2025)
This research is based on preliminary data from interviews with students at SMK IPT Karangpanas, which indicated that students perceive school counselors as having open and friendly personalities toward them. Students also stated that the counselor’s role is not limited to handling problematic students but also includes guiding and accompanying students, whether they are facing issues or are uncertain about choosing further studies. The purpose of this study is to determine: (1) how students perceive the counselor's personality competence, (2) students’ attitudes toward guidance and counseling services at school, and (3) whether there is a relationship between students' perceptions of the counselor's personality and their attitudes toward counseling services. The study involved 11th-grade students at SMK IPT Karangpanas as the population. Data collection methods used perception and attitude scales, while data analysis was conducted using descriptive statistics and product-moment correlation analysis. The results showed that students' perceptions of the counselor's personality competence fell into the fairly positive category, with an average score of 67.41. Similarly, students' attitudes toward counseling services were also fairly positive, with an average score of 60.75. The Pearson correlation test indicated a significant and positive relationship between students’ perceptions of the counselor’s personality competence and their attitudes toward guidance and counseling services, with a correlation coefficient of 0.542 and a significance value of 0.000 (p < 0.01). This means that the more positive students perceive the counselor’s personality, the more positive their attitude toward guidance and counseling services.